Comprehensive population-wide analysis of Lynch syndrome in Iceland reveals founder mutations in MSH6 and PMS2 - Sigurdis Haraldsdottir (Nature Portfolio, 2017)
Lynch syndrome is characterized by predisposition to colorectal cancer and mutations in genes involved in mismatch repair. Here, the authors use whole genome sequencing and immunohistochemistry of mismatch repair proteins to show a high prevalence of Lynch syndrome in the Icelandic population.